Effect of heavy metals to bacterial culture and the removal of heavy metals from an industrial effluent - Sannasi, P.; Salmijah, S.; Kader, J. (Biosciences Biotechnology Research Asia, 2010)
This paperreports the capability of consortium culture (CC) comprising of an acclimatizedmixed bacterial culture to withstand the toxic effect of Cr(VI), Cu, and Pb, at 1, 10, 100 mg/l and itsuptake, and to remove heavy metals from an industrial effluent. Consortium culture displayed goodheavy metal resistance (75-84.6%) on nutrient agar. Inverse of heavy metal toxicity index, B (l/mg)reflected CC’s ability to tolerate Cr(VI) concentration of up to 507.6 mg/l, followed by Pb at 348.43 mg/l and Cu at 243.90 mg/l. High metal uptake capacity was observed at 1 mg/l (q = 4.47-10.33 mg/g), 10mg/l (q = 29.27-96.07 mg/g) and 100 mg/ (q = 85.28-175.02 mg/g) in nutrient broth. Overall, metaltoxicity was in the order Cu > Pb > Cr(VI), and metal uptake was Pb > Cu > Cr(VI). X-ray fluorescencescreening indicated the abundance of Ca, K, P, and S on the biomass. Heavy metal removal studydemonstrated that CC was able to grow in waste effluent which was not subjected to any pre-treatmentor nutrient addition. Significantly higher metal removal in the range of 92-97.5% (P < 0.05) wasobtained for Cd, Cr(VI), Cu, Ni, and Pb with CC. Furthermore, CC was able to thrive and compete inthe presence of indigenous microbial population with no apparent decrease in metal removal capability.In conclusion, results establish the feasibility of employing CC to remove heavy metals from industrialeffluents and support the development of a bacterium-based integrated waste treatment system